Epigenetic Resources: Gaps in Aquatic Animal Germplasm Research - Fangcheng Li; Junfang Zhang; Xiangbing Cheng; Xinyao Cui; Jiamin Sun; Qigen Liu (Reviews in Aquaculture, 2025)
Aquatic animal germplasm research plays a vital role in biodiversity conservation and sustainable aquaculture. The traditional view is that diversity of germplasm resources is commonly attributed to genetic variation. However, recent studies in transgenerational epigenetics have shown that epigenetic information can also be passed down to offspring, which is consistent with the definition of germplasm. Therefore, it is necessary to define epigenetic information, such as DNA methylation, histone modifications, and ncRNAs, which can be passed down through generations, as epigenetic resources and incorporate them into the concept of germplasm. Germplasm resources should include not only genetic resources but also epigenetic resources. Epigenetic variation can arise from genetic, environmental, or stochastic factors. Genetic and epigenetic variation co‐determine phenotypic traits. It has been demonstrated that epigenetic information can be inherited across generations in aquatic animals. DNA methylation, histone modification, and ncRNAs are involved in addressing environmental challenges, maintaining genetic diversity, improving breeding strategies, combating inbreeding decline, and age determination. Therefore, future research on epigenetic resources is important for germplasm conservation, development, and utilization. This review proposes a new theoretical framework to elucidate the place of epigenetic resources in germplasm research and collects articles from the past 8 years that explore the inheritance of epigenetic information in aquatic animals. Integrating epigenetic research into germplasm studies enhances our understanding of population dynamics, adaptation, and evolutionary processes, thereby informing conservation strategies and enhancing aquaculture practices. By considering both genetic and epigenetic resources, we can address the challenges facing germplasm diversity and sustainable aquaculture more comprehensively.